The comparative evaluation of treatment outcomes in pediatric displaced supracondylar humerus fractures managed with either open or closed reduction and percutaneous pinning - Keskin, D; Sen, H (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2014)
PURPOSE OF THE STUDY: The aim of this study was to evaluate comparatively the outcomes of pediatric displaced supracondylar fractures of humerus which were treated with either closed reduction and percutaneous pinning (CRPP) or open reduction and percutaneous pinning (ORPP). MATERIAL AND METHODS: The study included 100 children with displaced supracondylar fractures of the humerus, who were treated with either CRPP (group 1) or ORPP (group 2); the numbers of subjects in the study groups were equal. The treatment outcomes were assessed clinically and radiologically. RESULTS: Ninety-six percent excellent or good cosmetic results were achieved in both groups, and 94% / 90% excellent or good functional results were achieved in groups 1 and 2 (respectively). There was no signifiant difference between Baumann and humero-capitellar angles of intact and operated sides in both groups, but there was an average carrying angle difference of 2,96 degrees in the group 1 and 1,52 degrees in the group 2 and these differences were statistically signifiant. Five cases (10%) from each group had superfiial pin tract infection. Hypertrophic incision scar occurred in 6 (12%) patients performed ORPP. CONCLUSION: Both CRPP and ORPP are successful treatment methods in the management of non-complicated and non-comminuted displaced supracondylar fractures of the humerus in pediatric ages and their outcomes are similar. Incision scar and the long duration of operation are the disadvantages of open surgery. For fiing the fracture, placement of two K-wires from the medial and lateral aspects which cross each other is enough to achieve a good stability. In ORPP practices, lateral incision is a simple and reliable approach despite of the dissatisfying scar tissue formation.
Keywords: výsledek terapie; intramedulární fixace fraktury; Male; Postoperative Complications; Child, Preschool; Infant; kostní hřeby; Child; radiografie; Fracture Fixation, Intramedullary; dítě; mužské pohlaví; pooperační komplikace; fraktury humeru; Treatment Outcome; předškolní dítě; Humeral Fractures; lidé; ženské pohlaví; Humans; kojenec; Bone Nails; Female; Radiography